Plant Foods and Underutilized Fruits as Source of Functional Food Ingredients Chemical Composition, Quality Traits, and Biological Properties - Donno, Dario; Turrini, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Changes in lifestyle and demographics shifted preferences about the relationships between food and health, contributing to generate new needs in the food supply. Today, the role of food is not only intended as hunger satisfaction and nutrient supply, but also as an opportunity to prevent nutrition-related diseases and improve physical and mental well-being. There is a growing interest in the novel or less well known plant foods that offer an opportunity for health maintenance. This book shows that an interest in plant foods and underutilized fruits is continuously growing, and agrobiodiversity exploitation offers effective and extraordinary potentialities. Readers will discover that plant foods could become an important source of health-promoting compounds and functional food ingredients with beneficial properties. The description of the quality and physicochemical traits, the identification and quantification of the main biologically active compounds, and the evaluation of their biological activities are important to assess plant food efficacy as functional foods or a source of food supplement ingredients for the consumers.